Menstrual and oral contraceptive cycle phases do not affect submaximal and maximal exercise responses - Mattu, A. T.; Iannetta, D.; MacInnis, M. J.; Doyle-Baker, P. K.; Murias, J. M. (Scandinavian Journal of Medicine & Science in Sports, 2020)
To examine whether the menstrual or monophasic oral contraceptive cycle phases affect submaximal (oxygen uptake (VO2) kinetics, maximal lactate steady-state (MLSS)) and maximal (VO2max, time-to-exhaustion (TTE)) responses to exercise in healthy, active women. During the mid-follicular or inactive-pill phase and the mid-luteal or active-pill phase of the respective menstrual or oral contraceptive cycle, 15 non-oral contraceptive users (mean and standard deviation (SD) (±): 27 ± 6 years; 171 ± 5 cm; 65 ± 7 kg) and 15 monophasic oral contraceptive users (24 ± 4 years; 169 ± 10 cm; 68 ± 10 kg) performed: one VO2 kinetics test; one ramp-incremental test; two to three 30-minute constant-load cycling trials to determine the power output corresponding to MLSS (MLSSp), followed by a TTE trial. The phase of the menstrual or oral contraceptive cycle did not affect the time constant of the V4O2 kinetics response (tVO2) (mid-follicular, 20 ± 5 seconds and mid-luteal, 18 ± 3 seconds; inactive-pill, 22 ± 8 seconds and active-pill, 23 ± 6 seconds), VO2max (mid-follicular, 3.06 ± 0.32 L min-1 and mid-luteal, 3.00 ± 0.33 L min-1; inactive-pill, 2.87 ± 0.39 L min-1 and active-pill, 2.87 ± 0.45 L min-1), MLSSp (mid-follicular, 181 ± 30 W and mid-luteal, 182 ± 29 W; inactive-pill, 155 ± 26 W and active-pill, 155 ± 27 W), and TTE (mid-follicular, 147 ± 42 seconds and mid-luteal, 128 ± 54 seconds; inactive-pill, 146 ± 70 seconds and active-pill, 139 ± 77 seconds) (P > .05). The rate of perceived exertion (RPE) at minute 30 of the MLSSp trials was greater in the mid-follicular phase (6.2 ± 1.5) compared with the mid-luteal phase (5.3 ± 1.4) for non-oral contraceptive users (P = .022). The hormonal fluctuations between the menstrual and oral contraceptive cycle phases had no detectable effects on submaximal and maximal exercise performance, even when RPE differed.